Alexander Borodin Contributions to Arts and Sciences - Igić, Rajko (Scripta Medica, 2023)
Alexander Borodin, a member of the Mighty Five composers, is presented. As an artist, due to his main compositions, Borodin got world fame. In contrast, his medical and scientific works and educational innovations are practically forgotten. We consider here: is there an objective way to compare the value of scientific and artistic creativity, including musical composing.
Keywords: Aleksandar Borodin; Komponovanje; Nauka; Medicina; Hemija